2007
DOI: 10.1255/ejms.896
|View full text |Cite
|
Sign up to set email alerts
|

Ion—Molecule Reactions Involving Methyl Isocyanide and Methyl Cyanide

Abstract: Ion-molecule reactions involving methyl isocyanide and methyl cyanide have been performed in a new rf-only hexapole collision cell inserted in a large-scale tandem mass spectrometer. Beside protonation processes, N-methyl cyanogen ions (CH(3)N(+)CCN) and 1-methyleneiminium-1- ethylenium ions (CH(2)CN(+)CH(2)) have been produced in high yield and fully characterized by high-energy collisional activation. The unimolecular chemistry of the molecular ions of caffeine (1,3,7-trimethyl xanthine) has been revisited o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…It was therefore initially supposed that the m/z 81 ions result from an interaction between neutral MIc and the [M -H] + ions of MIc, a similar reaction being reported for methyl cyanide. 2 However, in an experiment using a beam of decelerated m/z 40 ions and neutral MIc in the hexapole reaction cell, we have not found any convincing evidence for such a process, the major reaction observed being a proton transfer to MIc (m/z 42).…”
Section: (Carbon Monoxide) Of Methyl Isocyanidementioning
confidence: 61%
See 3 more Smart Citations
“…It was therefore initially supposed that the m/z 81 ions result from an interaction between neutral MIc and the [M -H] + ions of MIc, a similar reaction being reported for methyl cyanide. 2 However, in an experiment using a beam of decelerated m/z 40 ions and neutral MIc in the hexapole reaction cell, we have not found any convincing evidence for such a process, the major reaction observed being a proton transfer to MIc (m/z 42).…”
Section: (Carbon Monoxide) Of Methyl Isocyanidementioning
confidence: 61%
“…1 the same phenomenon was observed for the interaction between both ionized and neutral MIc affording new cumulenic ions. 2 Isonitriles (rN=c:) and also carbon monoxide (o=c:) formally belong to the general family of vinylidenes (r 2 c=c:). However, these particular compounds are stabilized by delocalisation of non-bonding electrons of nitrogen and oxygen resulting in a drastic shortening of the Nc and oc bonds.…”
Section: Journal Of Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Beside these thorough but limited studies, a need for the finding of other examples of nucleophilic aromatic substitution reactions is consequently evident in order to have a more general picture of this type of reaction and to provide new insight into its mechanism. In this context, we have recently shown that, in the gas phase, methyl isocyanide, CH 3 NC, is an efficient nucleophilic reagent toward cationic substrates. This is the result of its high ionization energy (11.24 eV) and its relatively low proton affinity (839 kJ mol −1 ), which prevent charge and proton exchange processes, respectively. Moreover, the high dipole moment of CH 3 NC (3.85 D) favors its association with charged species and consequently increases its reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%